Structural appraisal of baja prototype using resistive strain gauges and linear potentiometer - Pabllo Miguel Maia Pires; José Antônio da Silva; Júlio César Costa Campos; Antônio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Every machine or structural component undergoes a certain elastic deformation when exposed to some type of load or force. Furthermore, when it comes to the design and validation of components, a structural analysis plays a fundamental role, given the need to guarantee the integrity of the designed parts. To achieve this, reliable data is essential so that the entire process can be carried out in a coherent manner, based on engineering criteria. Therefore, the present study seeks to acquire dynamic or static loads and forces, which are present in main and critical components in a BAJA-type prototype, from the KomiKeto Baja Team - UFSJ, aiming to acquire data for the use of boundary conditions in numerical simulations, in addition to dynamic capture of loading cycles for subsequent fatigue analysis.